Pengaruh Harga, Lokasi, dan Kelengkapan Produk terhadap Loyalitas Konsumen di Toserba Yogya - Mochamad Faisal Akbar; Imam Nuryanto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
Customer loyalty plays a very significant role in the long-term success of a company. This is important because it can help the company increase sales volume, maintain market share, and strengthen long-term relationships with customers. Toserba Yogya, as one of the leading retailers, must understand the factors that influence customer loyalty in order to compete in an increasingly competitive market. This study aims to analyze the influence of price, location, and product completeness on customer loyalty at Toserba Yogya. This research is quantitative in nature and involves a population of customers who have shopped at Toserba Yogya at least twice. The research method used is a survey, with purposive sampling technique, where 100 respondents were selected based on specific criteria. The collected data were analyzed using multiple linear regression tests with the assistance of SPSS software. The results of this study indicate that price has a significant positive influence on customer loyalty, location does not have a significant influence on customer loyalty, and product completeness has a significant positive influence on customer loyalty.